Persepsi Wisatawan Domestik Terhadap Tingkat Keamanan di Daya Tarik Wisata Kawasan Luar Pura Uluwatu, Bali - Roswita, Elisabeth; Suryawan, Ida Bagus (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i01.p11, 2024)
The level of security outside Uluwatu Temple as a tourist attraction is less than optimal. Security is a very important point in the tourism industry. This is because security for every tourist is a determining factor in a tourist's decision to visit. For this reason, it is necessary to study whether domestic tourists' perceptions of the level of security in tourist attractions outside the Uluwatu Temple area are actually implemented or not. The aim of the research is to identify the characteristics of domestic tourists who visit tourist attractions in the outer area of Uluwatu Temple and measure domestic tourists' perceptions of the level of security in tourist attractions in the outer area of Uluwatu Temple. The research uses a quantitative paradigm which is deductive in nature with quantitative data methods and analysis. Data collection techniques include observation, surveys and documentation. The results of the research show that the perception of 50 domestic tourist respondents regarding the level of security in the area outside Uluwatu Temple is towards security facilities with an average frequency weighting value of 185 with the agree rating category and Security Managers with a frequency weighting average value of 113.4 with the disagree rating category. Managers of tourist attractions in areas outside Uluwatu Temple are expected to maintain the quality of security that has been implemented and need to improve security levels that are not yet optimal, such as increasing the number of security staff, repairing damaged security facilities, providing disaster detection equipment. Keywords: security, tourist perceptions, socio-demografis Characteristic